DYNAMICS OF MORBIDITY OF POPULATION IN IRKUTSK BETWEEN DURING SOCIO-ECONOMIC REFORMS - S. A. Korovin; D. V. Kulesh; V. A. Haptanova; V. P. Ilin; L. N. Lebedeva; A. G. Cherkashina (Acta Biomedica Scientifica, 2012)
This article presents an analysis of disease trends in selected age groups of the population of Irkutsk for the period of 1992-2009 and it is found that most of these trends are dependent on socio-economic factors. Built polynomial regression models revealed significant increase in morbidity of mental disorders in children, diseases of the nervous system and. the digestive system against opposing change prevalence of adolescent and. adult population for the analyzed period.